PERTANGGUNGJAWABAN PIDANA YANG DILAKUKAN OLEH KORPORASI DALAM PENCEMARAN LINGKUNGAN - Sofhan, Dedi; Multiwijaya, Vience Ratna; Suar, Aprima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: This research examines corporate criminal liability for environmental pollution, with a focus on the legal implications and factors that cause violations by corporations. The method used in this research is normative legal research, which analyzes applicable legal norms, legal principles, and doctrines related to law enforcement against corporations that commit pollution. The research results show that corporations can be held responsible for environmental pollution through criminal law mechanisms. Corporations are often involved in environmental violations due to economic motivation to gain quick profits, a moral crisis in organizational culture, weak supervision and law enforcement, and pressure to compete in the market. However, law enforcement against corporations involved in environmental crimes still faces many challenges, including the inability of the legal system to effectively accommodate corporate criminal liability. For this reason, a firm approach that includes the application of additional criminal sanctions and repair of environmental damage needs to be strengthened.Keywords: Environmental Pollution, Criminal and Corporate Liability.